TAP1 down-regulation elicits immune escape and poor prognosis in colorectal cancer. (2nd November 2017) - Ling, Agnes; Löfgren-Burström, Anna; Larsson, Pär; Li, Xingru; Wikberg, Maria L.; Öberg, Åke; Stenling, Roger; Edin, Sofia; Palmqvist, Richard
ABSTRACT: The anti-tumor immune response has been shown to be of great prognostic importance in colorectal cancer (CRC) and so has the tumors ability for immune evasion. Our aim of this study was to investigate tumor factors that influence immunity. We used a gene expression array to search for potential mechanisms of tumor immune escape. One candidate gene identified was TAP1, involved in antigen presentation by MHC class I. TAP1 protein expression was evaluated by immunohistochemistry in 436 CRC patients of the Colorectal Cancer in Umeå Study cohort. We found a significant association between a downregulated expression of TAP1 and low infiltration of various subtypes of lymphocytes as well as macrophages. A downregulated expression of TAP1 was further found to be independent of molecular characteristics, suggesting TAP1 down-regulation to reach beyond the well described highly immunogenic MSI CRCs. A low expression of TAP1 was also significantly associated with poor prognosis in patients with CRC, a result that stayed significant in tumor front of early stage tumors (stage I-II) through multivariable analyses. Furthermore, we found that TAP1 expression was inversely correlated with methylation at sites in close proximity to the promoter region. In summary, our results show down-regulation of TAP1 to be a general mechanism of tumor immune escape in CRC and a poor prognostic factor in stage I-II CRC patients. We also suggest that methylation of the TAP1 gene may be a putative mechanism for TAP1 downregulation.